2018
DOI: 10.1177/0022034517750592
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Optimum Fluoride Intake from Population-Level Evidence

Abstract: Policy on fluoride intake involves balancing caries against dental fluorosis in populations. The origin of this balance lies with Dean's research on fluoride concentration in water supplies, caries, and fluorosis. Dean identified cut points in the Index of Dental Fluorosis of 0.4 and 0.6 as critical. These equate to 1.3 and 1.6 mg fluoride (F)/L. However, 1.0 mg F/L, initially called a permissible level, was adopted for fluoridation programs. McClure, in 1943, derived an "optimum" fluoride intake based on this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…Eight critical reports were identified (1997-2010); a database search of 977 papers revealed further information from three studies that met the search criteria (GRADE assessment). 20 The critical reports all referred to the Dean studies in US cities during 1936-42 linking dental health and natural fluoride levels in water supplies. An Expert Working Group concluded there were no better data to use as a basis for establishing fluoride NRVs, as contemporary population studies were confounded by fluoridated toothpastes and/or products containing fluoride.…”
Section: Recent Evidence: Update On Nutrient Reference Values For Flumentioning
confidence: 99%
See 1 more Smart Citation
“…Eight critical reports were identified (1997-2010); a database search of 977 papers revealed further information from three studies that met the search criteria (GRADE assessment). 20 The critical reports all referred to the Dean studies in US cities during 1936-42 linking dental health and natural fluoride levels in water supplies. An Expert Working Group concluded there were no better data to use as a basis for establishing fluoride NRVs, as contemporary population studies were confounded by fluoridated toothpastes and/or products containing fluoride.…”
Section: Recent Evidence: Update On Nutrient Reference Values For Flumentioning
confidence: 99%
“…Two biomarkers were selected for the evidence review for infants and young children; dental caries and dental fluorosis, as measured by the dmf/DMF index and Dean’s index respectively. Eight critical reports were identified (1997–2010); a database search of 977 papers revealed further information from three studies that met the search criteria (GRADE assessment) . The critical reports all referred to the Dean studies in US cities during 1936–42 linking dental health and natural fluoride levels in water supplies.…”
Section: Introductionmentioning
confidence: 99%
“…264 As a result, the appropriateness of current guidance was addressed, however, no firm conclusions were made. [265][266][267]…”
Section: Adequate Intake Of Fluoridementioning
confidence: 99%
“…272 It is therefore not surprising that the guidelines on the AI of fluoride have been recently questioned 264 and addressed. [265][266][267] Based on the available literature, current recommendations on fluoride intake and the fact that the majority of fluoride benefits can be ascribed to its topical, rather than systemic, effects, it is hard to say whether the current AI is appropriate, i.e. too low or too high.…”
Section: Conclusion -Enough or Too Much Fluoride?mentioning
confidence: 99%
“…Furthermore, studies conducted using naturally fluoridated water supplies showed that at a fluoride concentration of 0.5–1.5 mg/L there was a reduction in caries, with no associated dental fluorosis or only questionable mottling of the teeth if the fluoride concentration exceeded 1 mg/L. However, when the fluoride concentration exceeds 1.5 mg/L in drinking water, it can cause dental mottling and discoloration, commonly known as dental fluorosis. Skeletal deformities have also been reported in known fluoride belts in range of countries following ingestion of 4–10mg/L of fluoride via drinking water.…”
Section: Introductionmentioning
confidence: 99%